DOI: 10.31274/rtd-180813-14300
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and situation awareness

Abstract: for their time and input into my dissertation. Thanks to all my subjects for giving their time to participate in my experiment. Thanks to Justin Recknor and Dongmei Zhai, graduate students from the Iowa State University Statistics department, for the help with the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…In this study, the increase in reaction time during the Stroop effect in SA-task correlated positively with the SA Index. This goes in line with the previous studies where delayed reaction times were observed when the font color and the word were different compared to when they were the same (Klamklay, 2002; Repov, 2004). This happens during the Stroop effect as the processing of a color impedes the simultaneous processing of a second stimulus attribute (word).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the increase in reaction time during the Stroop effect in SA-task correlated positively with the SA Index. This goes in line with the previous studies where delayed reaction times were observed when the font color and the word were different compared to when they were the same (Klamklay, 2002; Repov, 2004). This happens during the Stroop effect as the processing of a color impedes the simultaneous processing of a second stimulus attribute (word).…”
Section: Discussionsupporting
confidence: 92%
“…Past research (Jensen & Rohwer, 1966; Kang et al, 2013; Scarpina & Tagini, 2017) reported the application of the Stroop test in measuring cognitive functions, such as attention, processing speed, cognitive flexibility, and working memory. Specifically, Klamklay (2002), in their study, reported a high positive correlation of performance and SA with Stroop color and word test. Despite these works, there are many questions that are still needed to be addressed for a better understanding of the maintenance of SA.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation